Bite Force Transducers and Measurement Devices - Gu, Yingzhi; Bai, Yuxing; Xie, Xianju (Frontiers in Bioengineering and Biotechnology, 2021)
In dental research, bite force has become an important curative effect evaluation index for tooth restoration, periodontal treatment, and orthodontic treatment. Bite force is an important parameter to evaluate the efficacy of the masticatory system. Physicians obtain the therapeutic basis for occlusal adjustment by measuring the bite force and the dynamic changes in occlusal contact at different stages of treatment and objectively evaluate the therapeutic effect. At present, many devices are used to record the bite force. Most of these devices use force transducers to detect bite force, such as strain gauge transducers, piezoresistive transducers, piezoelectric transducers, optical fiber transducers, and pressure-sensitive films. This article summarizes the various equipment used to record bite force, related materials and the characteristics of this equipment. It provides a reference for physicians to make choices during the clinical process and at the same time provides a basis for the development of new occlusal force measurement materials.